2023
DOI: 10.3390/jfb14030164
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Premixed Calcium Silicate Bioceramic Sealer with Warm Carrier-Based Technique: A 2-Year Study for Patients Treated in a Master Program

Abstract: Background: Recently several calcium silicate flowable sealers have been introduced as endodontic materials for the root canal. This clinical study tested the use of a new premixed calcium silicate bioceramic sealer in association with the Thermafil warm carrier-based technique (TF). Epoxy-resin-based sealer with the warm carrier-based technique was the control group. Methodology: Healthy consecutive patients (n = 85) requiring 94 root canal treatments were enrolled in this study and assigned to one filling gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 78 publications
1
15
0
Order By: Relevance
“…This discrepancy may be due to the fact that the cell viability experiments were only performed at 24-48 h, which does not allow sufficient exposure time to observe the cellular response to this treatment. Another reason could be attributed to the non-complete set of materials, also confirmed in recent clinical studies, which highlighted the occurrence of a not stable seal in the periapical area (Zamparini et al, 2023). In agreement with our results, another study reported that Endosequence BC Sealer and TFbc had better cell viability rates at 72 h than AHPbc using human periodontal cells (Kwak et al, 2023).…”
Section: Alizarin Red Stainingsupporting
confidence: 91%
“…This discrepancy may be due to the fact that the cell viability experiments were only performed at 24-48 h, which does not allow sufficient exposure time to observe the cellular response to this treatment. Another reason could be attributed to the non-complete set of materials, also confirmed in recent clinical studies, which highlighted the occurrence of a not stable seal in the periapical area (Zamparini et al, 2023). In agreement with our results, another study reported that Endosequence BC Sealer and TFbc had better cell viability rates at 72 h than AHPbc using human periodontal cells (Kwak et al, 2023).…”
Section: Alizarin Red Stainingsupporting
confidence: 91%
“…Recent studies confirmed that warmcarrier-based systems may induce a great percentage of extrusion, ranging from approx. 25% to 58% of the cases [23,29]. A conventional gold-standard sealer (AH Plus), mainly composed of epoxy-resin components, offered a high percentage of radiographic extrusion (30%) [23], likely attributable to the higher flow when heating is applied [34].…”
Section: Discussionmentioning
confidence: 99%
“…Despite their promising characteristics and considering the recent introduction on the market, a limited number of short-term clinical investigations have been conducted [9,[22][23][24]. Further research is needed to fully understand their performance, clinical outcomes, and occurrence of post-operative pain after filling.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, 82% of cases obturated with AHB using a carrier-based technique (Thermafil; Dentsply, Konstanz, Germany) exhibited complete healing after 1 year [28]. Comparable success rates have been reported for premixed CSCSs and an epoxy resin-based sealer (AH Plus, Dentsply Sirona) when used in warm vertical compaction using the SuperEndo System (B&L Biotech, Ansan, Republic of Korea) at 150 • C [26] or the Thermafil technique [29]. Further investigation is still warranted due to the paucity of well-controlled long-term studies.…”
Section: Introductionmentioning
confidence: 98%
“…Regarding the clinical impact of heat application to premixed CSCSs, a few studies have reported favorable short-term outcomes [26][27][28][29]. In one study, a 1-year success rate of 99% was reported when four brands of premixed CSCSs were used with either the continuous wave of condensation technique or the carrier-based technique [27].…”
Section: Introductionmentioning
confidence: 99%